Morphological Transformations and Microclimatic Impacts in Urban Canyons: A Spatial and Temporal Analysis in Vila Rodrigues, Passo Fundo, Brazil - Caino , Isadora Cezar; Braz, Jéssica; Silva, Manoela Peruzzo da; Vidmar, Rangel Girardelo; Cardoso, Grace Tibério (Scientific Journal ANAP, 2025)
Objective – This article aims to analyze the morphology of urban canyons in the Vila Rodrigues neighborhood, located in Passo Fundo, RS, by investigating morphological transformations over time and their relationship with land surface temperatures. Methodology – The research adopts an empirical approach, based on the morphometric analysis of the urban configuration (H/W ratio, building density, presence of vegetation) associated with land surface temperature (LST) data obtained through remote sensing. The analysis focuses on the neighborhood scale, allowing for a detailed spatial and temporal reading of morphological changes and their microclimatic impacts. Originality/relevance – The study addresses a theoretical gap related to the scarcity of microclimatic analyses at the neighborhood scale, especially in medium-sized cities such as Passo Fundo-RS. Its academic relevance lies in contributing to a deeper understanding of the relationship between urban morphology and local climate, with a focus on specific and rapidly transforming urban areas like Vila Rodrigues. Results – The main results indicate that significant morphological transformations in the neighborhood, such as increased verticalization and building density, are associated with rises in surface temperatures. The replacement of vegetated areas by impervious surfaces contributes to the intensification of urban heat islands. Theoretical/methodological contributions – The study contributes theoretically by reinforcing the importance of integrated analysis between urban form and local climate, using remote sensing data and morphometric parameters. Methodologically, it proposes a replicable approach for urban environmental diagnostics at the neighborhood scale, with potential for application in various territorial contexts. Social and environmental contributions – From a social and environmental perspective, the study offers technical support for the development of more effective public policies to mitigate the effects of climate change, focusing on improving thermal comfort and reducing the vulnerability of urban populations.